P30-58 Extraction and Evaluation of Latent Representations from Peripheral Blood Smear Images - T. Iwasaka; T. Mizuno; K. Morita; I. Azuma; E. Nakashima; H. Kusuhara (Toxicology Letters, 2025)

P12-08 Establishment of a novel and simple drinking water liver injury model for hepatotoxicity research - T. Iwasaka; T. Mizuno; K. Morita; I. Azuma; T. Nakagawa; E. Nakashima; H. Kusuhara (Toxicology Letters, 2024)

Cell-Permeable Calpain Inhibitor SJA6017 Provides Functional Protection to Spinal Motoneurons Exposed to MPP+ - Supriti Samantaray; Varduhi H. Knaryan; Angelo M. Del Re; John J. Woodward; Donald C. Shields; Mitsuyoshi Azuma; Jun Inoue; Swapan K. Ray; Naren L. Banik (Neurotoxicity Research, 2020)

Evaluation of microelement contents in Clethra barbinervis as food for human and animals in contrasting geological areas - Asako K. Azuma; Rie Tomioka; Chisato Takenaka (Environmental Geochemistry and Health, 2016)

Occlusal Disharmony Increases Amyloid-β in the Rat Hippocampus - D. Ekuni; T. Tomofuji; K. Irie; T. Azuma; Y. Endo; K. Kasuyama; M. Morita (NeuroMolecular Medicine, 2011)

Breeding system, colony and population structure in the weaver ant Oecophylla smaragdina - E.A. SCHLÜNS; B.J. WEGENER; H. SCHLÜNS; N. AZUMA; S. K. A. ROBSON; R. H. CROZIER (Molecular Ecology, 2009)
Weaver ants ( Oecophylla smaragdina ) are dominant ants in open forests from India, Australia, China and Southeast Asia, whose leaf nests are held together with larval silk. The species, together with its sole congener O. longinoda , has been important in research on biological control, communication, territoriality and colony integration. Over most of the range, only one queen has been found per colony, but the occurrence of several queens per nest has been reported for the Australian Northern Territory. The number of males mating with each queen is little known. Here we report on the colony structure of O. smaragdina using published and new microsatellite markers. Worker genotype arrays reflect the occurrence of habitual polygyny (more than one queen per colony) in 18 colonies from Darwin, Northern Australia, with up to five queens inferred per colony. Monogyny (one queen per colony) with occasional polygyny was inferred for 14 colonies from Queensland, Australia, and 20 colonies from Java, Indonesia. Direct genotyping of the sperm carried by 77 Queensland queens and worker genotypic arrays of established colonies yielded similar results, indicating that less than half of the queens mate only once and some mate up to five times. Worker genotype arrays indicated that queens from Java and the Northern Territory also often mate with more than one male, but less often than those from Queensland. A strong isolation‐by‐distance effect was found for Queensland samples. The variation uncovered means that O. smaragdina is a more versatile study system than previously supposed.

Synchronized development of gonad and bioluminescent light organ in a highly sexually dimorphic leiognathid fish, Photoplagios rivulatus - K. Ikejima; M. Wada; K. Kita-Tsukamoto; T. Yamamoto; N. Azuma (Marine Biology, 2008)

Genetic structure of masu salmon ( Oncorhynchus masou ) populations in Hokkaido, northernmost Japan, inferred from mitochondrial DNA variation - S. Kitanishi; K. Edo; T. Yamamoto; N. Azuma; O. Hasegawa; S. Higashi (Journal of Fish Biology, 2007)
Genetic structure of masu salmon Oncorhynchus masou populations in Hokkaido was examined by analysing mtDNA NADH dehydrogenase subunit 5 gene (561 bp) of 382 individuals collected from 12 rivers, in which there were no records of artificial release. Analysis of molecular variance showed that between groups level and between populations within‐group level explained each c. 10% of genetic variance. In neighbour‐joining tree, four populations located in southern Hokkaido were clustered into a single group; however, other populations did not form any clear clusters. Fu’s F S , Tajima’s D and a mismatch distribution test indicated a sudden expansion of population in the entire population of Hokkaido and the northernmost population of Chiraibetsu, which was genetically close to the southern Hokkaido group. The Sea of Japan and southern rivers, including those of southern Hokkaido, seem to have served as refugia for masu salmon during glacial periods, and their dispersal and straying in interglacial periods affected the genetic structure of masu salmon populations in Hokkaido.

High-throughput DNA typing of HLA-A, -B, -C, and -DRB1 loci by a PCR–SSOP–Luminex method in the Japanese population - Yoshiki Itoh; Nobuhisa Mizuki; Tsuyako Shimada; Fumihiro Azuma; Mitsuo Itakura; Koichi Kashiwase; Eri Kikkawa; Jerzy K. Kulski; Masahiro Satake; Hidetoshi Inoko (Immunogenetics, 2005)

The MHC classI linkage group is a major determinant in the in vivo rejection of allogeneic erythrocytes in rainbow trout (Oncorhynchus mykiss) - Md. Rafiqul Islam Sarder; Uwe Fischer; Johannes Martinus Dijkstra; Ikunari Kiryu; Yasutoshi Yoshiura; Teruo Azuma; Bernd Kllner; Mitsuru Ototake (Immunogenetics, 2003)

The MHC classI linkage group is a major determinant in the in vivo rejection of allogeneic erythrocytes in rainbow trout (Oncorhynchus mykiss) - Ikunari Kiryu; Yasutoshi Yoshiura; Teruo Azuma; Bernd Kllner; Mitsuru Ototake; Md.RafiqulIslam Sarder; Uwe Fischer; JohannesMartinus Dijkstra (Immunogenetics, 2003)

Calf and shin muscle oxygenation patterns and femoral artery blood flow during dynamic plantar flexion exercise in humans - S. Shimizu; F. Chiarotti; M. Ferrari; A. Kagaya; V. Quaresima; S. Homma; K. Azuma (European Journal of Applied Physiology, 2001)

Circadian variation of the urinary 6β-hydroxycortisol to cortisol ratio that would reflect hepatic CYP3A activity - M. Ohno; I. Yamaguchi; T. Ito; K. Saiki; I. Yamamoto; J. Azuma (European Journal of Clinical Pharmacology, 2000)

Localization and effects of hepatocyte growth factor on smooth muscle cells during neointimal formation after balloon denudation - Masaru Aoyagi; Shinji Yamamoto; Hiroshi Azuma; M. Yamamoto; Masashi Tamaki; Yasunari Niimi; Kimiyoshi Hirakawa; K. Yamamoto (Histochemistry and Cell Biology, 1999)

Interaction of citrus juices with pranidipine, a new 1,4-dihydropyridine calcium antagonist, in healthy subjects - K. Hashimoto; T. Shirafuji; H. Sekino; O. Matsuoka; H. Sekino; O. Onnagawa; T. Okamoto; S. Kudo; J. Azuma (European Journal of Clinical Pharmacology, 1998)

Immunolocalization of matrix metalloproteinases in rabbit carotid arteries after balloon denudation - Masaru Aoyagi; Mari Yamamoto; Hiroshi Azuma; Goro Nagashima; Yasunari Niimi; Masashi Tamaki; Kimiyoshi Hirakawa; K. Yamamoto (Histochemistry and Cell Biology, 1998)

Characterization of neutralizing monoclonal antibody escape mutants of Hantaan virus 76118 - M. Kikuchi; K. Yoshimatsu; J. Arikawa; R. Yoshida; Y.-C. Yoo; Y. Isegawa; K. Yamanishi; S. Tono-oka; I. Azuma (Archives of Virology, 1998)

The treatment with differentiation- and apoptosis-inducing agent, vesnarinone, of a patient with oral squamous cell carcinoma - M. Sato; K. Harada; Y. Yura; M. Azuma; H. Kawamata; H. Iga; H. Tsujimoto; H. Yoshida; M. Adachi (Apoptosis, 1997)

Changes in osteopontin mRNA expression during phenotypic transition of rabbit arterial smooth muscle cells - Mari Yamamoto; Masaru Aoyagi; Hiroshi Azuma; K. Yamamoto (Histochemistry and Cell Biology, 1997)

Pharmacokinetics of an antifibrotic agent, pirfenidone, in haemodialysis patients - M. Taniyama; S. Ohbayashi; M. Narita; R. Nakazawa; S. Hasegawa; N. Azuma; S. Teraoka; K. Ota; S. Yamauchi; S. B. Margolin (European Journal of Clinical Pharmacology, 1997)

Therapy for oral squamous cell carcinoma by tegafur and streptococcal agent OK-432 in combination with radiotherapy: Association of the therapeutic effect with differentiation and apoptosis in the cancer cells - M. Sato; K. Harada; H. Yoshida; Y. Yura; M. Azuma; H. Iga; T. Bando; H. Kawamata; Y. Takegawa (Apoptosis, 1997)

Protective immunity of Hantaan virus nucleocapsid and envelope protein studied using baculovirus-expressed proteins - K. Yoshimatsu; Y-C. Yoo; R. Yoshida; C. Ishihara; I. Azuma; J. Arikawa (Archives of Virology, 1993)